Tweeting to the Choir: Online Performance and Academic Identity - singh, sava saheli (AoIR Selected Papers of Internet Research, 2013)
New academic practices supported by platforms like Twitter give scholars the opportunity to carve out professional identities at a time when the expectations of them in an increasingly competitive academic marketplace have never been higher. Networked academic communities magnify the reach and impact of scholarly work, as well as support professional connections. Propagating publications – both traditional and non-traditional – via Twitter and creating platform-specific artifacts like “storified” conversations, are things scholars seeking to legitimize alternative forms of scholarship do to give voice to their dissatisfactions. While ostensibly fostering a climate of openness that has the potential to disrupt the status quo in academia, these practices run the risk of creating insular groups of scholars – an outcome contrary to the very things such scholars profess to be trying to achieve.